Validating the Capability for Measuring Age-Related Changes in Grip-Force Strength Using a Digital Hand-Held Dynamometer in Healthy Young and Elderly Adults. (21st April 2020) - Lee, Shu-Chun; Wu, Li-Chen; Chiang, Shang-Lin; Lu, Liang-Hsuan; Chen, Chao-Ying; Lin, Chia-Huei; Ni, Cheng-Hua; Lin, Chueh-Ho
Abstract : Background . Grip-force performance can be affected by aging, and hand-grip weakness is associated with functional limitations of dasily living. However, using an appropriate digital hand-held dynamometer with continuous hand-grip force data collection shows age-related changes in the quality of hand-grip force control may provide more valuable information for clinical diagnoses rather than merely recording instantaneous maximal hand-grip force in frail elderly adults or people with a disability. Therefore, the purpose of this study was to indicate the construct validity of the digital MicroFET3 dynamometer with Jamar values for maximal grip-force assessments in elderly and young adults and confirmed age-related changes in the maximal and the quality of grip-force performance using the MicroFET3 dynamometer in elderly people. Methods . Sixty-five healthy young (23.3 ± 4.5   years ) and 50 elderly (69.5 ± 5.8   years ) adults were recruited and asked to perform a validity test of the grip-force maximum voluntary contraction (MVC) using both the dominant and nondominant hands with a Jamar dynamometer and a MicroFET3 dynamometer. Results . A strong correlation of maximal grip-force measurements was found between the MicroFET3 dynamometer and Jamar standard dynamometer for both hands in all participants (p < 0.05 ). Although, the results showed that a lower grip force was measured in both hands by the MicroFET3 dynamometer than with the Jamar dynamometer by 49.9%~57% (p < 0.05 ), but confidently conversion formulae were also developed to convert MicroFET3 dynamometer values to equivalent Jamar values for both hands. Both dynamometers indicated age-related declines in the maximum grip-force performance by 36.7%~44.3% (p < 0.05 ). We also found that the maximal hand-grip force values generated in both hand by the elderly adults were slower and more inconsistent than those of the young adults when using the MicroFET3 dynamometer. Conclusions . This study demonstrated that the digital MicroFET3 dynamometer has good validity when used to measure the maximal grip force of both hands, and conversion formulae were also developed to convert MicroFET3 dynamometer force values to Jamar values in both hands. Comparing with the Jamar dynamometer for measuring grip force, the MicroFET3 dynamometer not only indicated age-related declines in the maximum grip-force performance but also showed slower and more inconsistent maximal hand-grip strength generation by the elderly.